2006
DOI: 10.1111/j.1745-7939.2006.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for geography in the New Zealand senior secondary school in the context of current curriculum developments

Abstract: Current curriculum developments will provide a new framework for the teaching of social sciences, including geography, in New Zealand secondary schools. This article outlines recent challenges faced by the subject, and the development and likely nature of the new curriculum. Some ways in which teachers can plan and implement innovative programmes within the framework of the existing syllabus and the new curriculum are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The current Ministry of Education policy devolves curriculum decision making to schools, rather than providing a centrally prescribed curriculum. Assuming such a vision is not entirely straight‐jacketed by the assessment parameters of NCEA, this presents a possibility for teachers to respond creatively to the broad conceptual framework offered by the revised New Zealand Curriculum (Baldwin & Papprill 2006). However, it would be naïve to expect that all teachers have such capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The current Ministry of Education policy devolves curriculum decision making to schools, rather than providing a centrally prescribed curriculum. Assuming such a vision is not entirely straight‐jacketed by the assessment parameters of NCEA, this presents a possibility for teachers to respond creatively to the broad conceptual framework offered by the revised New Zealand Curriculum (Baldwin & Papprill 2006). However, it would be naïve to expect that all teachers have such capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It is designed to ensure that they have the tools and knowledge to make a difference in their community if they so desire. The gaining of credits [for passing an achievement standard] on the way is a bonus, but not the main outcome.’ (Baldwin & Papprill 2006: 214).…”
Section: Historical Constructions Of the Term ‘Development’mentioning
confidence: 99%
“…Roger Baldwin and Jocelyn Papprill have observed that many schools create a geography matrix of the available achievement standards to plan their year's course. They suggest that the revised curriculum allows for a much wider approach to be taken by teachers in planning a year's course, so that assessment is a by-product of the learning that takes place (Baldwin & Papprill 2006). There is an example given of a school that has chosen to have themes for each term.…”
Section: Implications For the Learnermentioning
confidence: 99%